Teologi Pendidikan Dalam Perjanjian Lama (Kitab Meleakhi) - Fanny Yapi Markus Kaseke; Nita Rahayun (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2022)
This paper is about the biblical foundation for Christian education, the foundation found in the Old Testament, namely the book of Malachi. Christian education requires a foundation that comes from the Bible, in which it displays Christian values. Many Christian Educational Institutions, educators (teachers), students do not have sufficient "supplies" in the administration of Christian education, so it is as if the knowledge being studied stands alone, and has nothing to do with existing Christian values. in the Bible. So the purpose of this study is to present the value of Christian education from the Bible which comes from the book of Malachi. The method used in this research is descriptive qualitative method, where the qualitative approach here is quasi-qualitative. Descriptive description is done by exposing the parts of the Bible that are in the book of Malachi. The method of interpretation used is exegesis. The verses or phrases or sentences or parts that are executed are verses/phrases/sentences/sections that the author considers to contain things that have to do with Education.